Pelatihan Pengelolaan Sampah Berbasis Masyarakat Di Kelurahan Kampung Makassar Timur - Nani Nagu; Lita Asyriati Latif (Universitas Khairun, 2021)
One of the areas in Ternate City, namely Kampung Makasar Timur, where most of the population live above the water, so it seems that this area looks slum because there is no good solid and liquid domestic waste management system. This problem needs to be overcome by systematic, comprehensive, and sustainable waste management which includes reducing and handling waste from its source, namely the community. The purpose of this activity is to help the community by providing explanations and. increasing public insight about the household waste management system, the environment, increasing community participation in the waste management system and promoting household-based waste management as an effort to preserve the environment, this community service activity begins by observing the location of community service to determine the source and volume of waste generation , take an approach to the community, especially among housewives through Dasawisma activities then provide guidance and counseling, to increase awareness and community participation in waste management by utilizing community gathering media at the kelurahan location. Furthermore, he taught the community how to sort waste by type by making Takakura baskets as a household compost producer.